Ultrasonic extraction of Xinjiang Changyan coal and GC/MS analysis of its soluble compounds - Zhou, J.; Shi, C-L. (Energy sources. Part A, Recovery, utilization, and environmental effects, 2017)
In order to investigate the compositions of soluble organic compounds in low-rank coals, Xinjiang Changyan coal (XCC) was selected in this subject. On this basis, XCC was made to undergo ultrasonic extraction (UE) in a mixed solvent toluene/ethanol with synergistic effect and the soluble mixture was analyzed with gas chromatography/mass spectrometry (GC/MS). Sixty-three organic compounds including aliphatic hydrocarbons, arenes, and organoheteratom compounds were detected. The analysis of these high-valued organic compounds from soluble XCC can provide an important theoretical basis for nonfuel of low-rank coals.